Flexible graphene-based neurotechnology for high-precision deep brain mapping and neuromodulation in Parkinsonian rats - Nicola Ria; Ahmed Eladly; Eduard Masvidal-Codina; Xavi Illa; Anton Guimerà; Kate Hills; Ramon Garcia-Cortadella; Fikret Taygun Duvan; Samuel M. Flaherty; Michal Prokop; Rob. C. Wykes; Kostas Kostarelos; et al. (Nature Communications)
Abstract Deep brain stimulation (DBS) is a neuroelectronic therapy for the treatment of a broad range of neurological disorders, including Parkinson’s disease. Current DBS technologies face important limitations, such as large electrode size, invasiveness, and lack of adaptive therapy based on biomarker monitoring. In this study, we investigate the potential benefits of using nanoporous reduced graphene oxide (rGO) technology in DBS, by implanting a flexible high-density array of rGO microelectrodes (25 µm diameter) in the subthalamic nucleus (STN) of healthy and hemi-parkinsonian rats. We demonstrate that these microelectrodes record action potentials with a high signal-to-noise ratio, allowing the precise localization of the STN and the tracking of multiunit-based Parkinsonian biomarkers. The bidirectional capability to deliver high-density focal stimulation and to record high-fidelity signals unlocks the visualization of local neuromodulation of the multiunit biomarker. These findings demonstrate the potential of bidirectional high-resolution neural interfaces to investigate closed-loop DBS in preclinical models.